A in(con)clusão na subjetividade do docente de matemática: (trans)formação a partir do encontro com aluno surdo - Matos, Efraim de Alcântara (2024)
This thesis, structured in a multipaper format, seeks to understand the process of (trans)formation of mathematics teachers in their encounters with deaf students. Grounded in French Discourse Analysis (DA) and Schizoanalysis, the research explores teacher subjectivity as a dynamic and relational construct, continuously shaped by interaction with others and influenced by perceptions of self, others, mathematics, and deafness. Mathematics, approached as a language that goes beyond its instrumental function, directly influences teachers' subjectivation, particularly in the context of inclusive education, where their beliefs are mobilized in various directions. Deafness is discussed as a cultural characteristic, but other perspectives are also highlighted, challenging the hegemonic forms of traditional pedagogical practices, requiring new forms of subjectivation and reconfiguring teachers' identities and conceptions about it. The methodology used includes the analysis of teachers' narratives through DA and schizoanalytic cartography, focusing on their experiences teaching mathematics to deaf students. This allows for mapping some of the subjective transformations that arise from this encounter. The results show that contact with deaf students significantly transforms pedagogical practices and teachers' perceptions of themselves and others, demanding creative adaptations and critical reflections on the role of the teacher and on inclusion, as well as considerations on teacher education. In terms of public policy, although legal frameworks and inclusive devices (laws, decrees, regulations, guidelines, etc.) play an important role, they are often seen as insufficient to ensure effective inclusion from the teachers' perspective. Therefore, the research provides relevant contributions to the field of teacher education, suggesting that encounters with difference, such as deafness, can serve as catalysts for pedagogical innovations and transformations in the identity and practices of mathematics teachers.